LEARNING EXPERIENCES OF THE STUDENTS IN ETWINNING PROJECTS - Luminiţa CATANĂ; Angelica MIHĂILESCU (Revista de Pedagogie, 2022)
The article highlights the students’ perspective regarding their experience with eTwinning, their investment of resources, their expectations, as well as the academic and personal outcomes obtained as a result of their involvement. The students’ opinions about the collaborative dimension of these projects in new learning contexts, the effectiveness of communication, the perspectives of personal development, the skills they developed, the well-being, and the motivation for learning are analyzed. The current article is based on a secondary analysis of data collected in a research project carried out in 2021 on a sample of 921 secondary and high school students, which aimed to assess the effects of the eTwinning project in Romania. The article focuses on the analysis of qualitative data regarding the learning experiences that the eTwinning project provided to the participating students.